Illocutionary Speech in Sampa' Tongkonan Discourse as an Oral Tradition of the Toraja People - Anastasia Baan (Ranah: Jurnal Kajian Bahasa, 2023)
This study aimed to explore the meaning of illocutionary speech acts in the discourse of Sampa' Tongkonan, which is an oral tradition of the Toraja people. The researchers employed qualitative research methodology to collect data through interviews, observations, and documentation. The data analysis technique involved identifying, analyzing and describing the meaning of illocutionary speech. The study found that the illocutionary speech acts present in the Sampa' Tongkonan discourse were expressive, declarative, and directive. Expressive illocutionary utterances were used to express gratitude for the family clump, while declarative illocutionary speech was used to make statements to all family clumps. Directive illocutionary speech was used to make an appeal to the entire family. The study provides insights into the meaning of illocutionary speech in the Sampa' Tongkonan discourse as an oral tradition of the Toraja people. The findings have implications for the preservation and promotion of the Toraja culture. This study is significant because it sheds light on the unique cultural practices of the Toraja people and their oral tradition. It highlights the importance of understanding the meaning of illocutionary speech in the Sampa' Tongkonan discourse, which is an essential part of the Toraja culture. The study also provides a framework for future research on illocutionary speech in other oral traditions of the Toraja people. In conclusion, this study contributes to the understanding of the illocutionary speech acts present in the Sampa' Tongkonan discourse. The findings have implications for the preservation and promotion of the Toraja culture.  AbstrakPenelitian ini bertujuan untuk mengeksplorasi makna dari tindak tutur ilokusi dalam wacana Sampa' Tongkonan, yang merupakan tradisi lisan dari masyarakat Toraja. Peneliti menggunakan metodologi penelitian kualitatif untuk mengumpulkan data melalui wawancara, observasi, dan dokumentasi. Teknik analisis data melibatkan identifikasi, analisis, dan deskripsi makna dari tindak tutur ilokusi. Studi ini menemukan bahwa tindak tutur ilokusi yang hadir dalam wacana Sampa' Tongkonan adalah ekspresif, deklaratif, dan direktif. Ucapan ilokusi ekspresif digunakan untuk mengungkapkan rasa terima kasih untuk kelompok keluarga, sedangkan ucapan ilokusi deklaratif digunakan untuk membuat pernyataan kepada semua kelompok keluarga. Ucapan ilokusi direktif digunakan untuk membuat sebuah permohonan kepada seluruh keluarga. penelitian ini memberikan wawasan tentang makna tindak tutur ilokusi dalam wacana Sampa' Tongkonan sebagai tradisi lisan dari masyarakat Toraja. Temuan ini memiliki implikasi untuk pelestarian dan promosi budaya Toraja. Studi ini penting karena memberikan gambaran tentang praktik budaya unik dari masyarakat Toraja dan tradisi lisan mereka. Studi ini juga memberikan kerangka kerja untuk penelitian masa depan tentang tindak tutur ilokusi dalam tradisi lisan lain dari masyarakat Toraja. Secara keseluruhan, studi ini memberikan kontribusi pada pemahaman tentang tindak tutur ilokusi yang hadir dalam wacana Sampa' Tongkonan. Temuan ini memiliki implikasi untuk pelestarian dan promosi budaya Toraja. Studi ini memberikan wawasan berharga tentang praktik budaya unik dari masyarakat Toraja dan tradisi lisan mereka. Metodologi penelitian yang digunakan dalam penelitian ini dapat direplikasi dalam penelitian masa depan tentang tindak tutur ilokusi dalam tradisi lisan lain dari masyarakat Toraja.